Aquaculture Production And Employee Wellness Between Brackish Water And Freshwater Farmers In Penang State - Zain, Nur Syafiqah Mat (2023)
Introduction: Aquaculture is seen as an essential food-producing sector for improving global food security and nutrition indices. The sustainability of the aquaculture industry depends strongly on the space, environment, ecology, economy, industry, human behaviour and the policy. Nevertheless, the overall aquaculture industry inherent lack of professional guidance and technical efficiency, and the intention of sustainable technologies utilization is often underreporting. This cross-sectional study evaluated the aquaculture stakeholders’ adoption readiness, perceived behaviour and determinant barriers towards sustainable aquaculture technologies. The study also examined the health complaints, mental status and quality of life of aquaculture workers. Methodology: A list of registered aquaculture farms was obtained from the Penang State Fisheries Department. Subsequently, an invitation letter was issued officially to all the listed aquaculture stakeholders, followed by individual telephone calls and research intention briefing. Aquaculture stakeholders were interviewed, and information about production trend, sales, management, technology adoption readiness, and barriers were gathered. The aquaculture workers' health complaints were collected, and mental health status was evaluated as means of depression, anxiety, stress and self-esteem. Self-perceived quality of life was assessed using a structured questionnaire. Results: The study involved the participation of 88 (84.6%) brackish water and 16 (15.4%) freshwater aquaculture stakeholders